Octreotide treatment in a neonate with non-chylous pleural effusion - Salih Kalay; Osman Oztekin; Gonul Tezel; Burak Emre Demir; Mustafa Akcakuş; Nihal Oygur (Wolters Kluwer Medknow Publications, 2013)
Fetal pleural effusion is a rare condition. While it may regress spontaneously, it may also continue up to the post-natal period. This condition may be treated by thoracentesis, thoracoabdominal shunt application and pleurodesis in the intrauterine period while thoracentesis or tube thoracostomy may be used in the post-natal period. In cases where the fluid is defined to represent chylothorax, octreotide, a somatostatin analogue, may be administered for treatment. In this case report, we discussed the outcomes of treatment with octreotide administered in a neonatal case under follow-up due to fetal pleural effusion and with non-chylous ascites detected in the post-natal period.